ABS copolymer-activated carbon mixed matrix membranes for CO 2/CH4 separation - Anson, Marcia (2004)
The performance of various novel mixed matrix composite (MMC) membranes for separation of CO2 from CH4 was investigated as a function of carbon loading. Acrylonitrile-butadiene-styrene (ABS) copolymer was used as the polymer matrix and two micro-mesoporous activated carbons (AC) were chosen as inorganic fillers. A thorough analysis of the effect of temperature and pressure on the permeation rates of CO2 and CH4 and selective properties of the ABS-AC composite membranes was done. Measurements were made for each system at four different temperatures in the range 20-50 °C, and in the feed pressure range from 2 to 8 × 105 Pa. The ABS-AC membranes showed a simultaneous increase of CO2 gas permeabilities (40-600%) and CO2/CH4 selectivities (40-100%) over the intrinsic ABS permselectivity by increasing the percentage of carbon loaded in the mixed matrix composite membrane.